Validity and Feasibility of Interactive Multimedia on Sublimation Topics Oriented toward Chemical Literacy - Risa Rahmawati Sunarya; Dhea Setiani; Ida Farida (CV. Generasi Intelektual Digital (GEN ID), 2026)
ABSTRACT Sublimation is one of the chemistry topics that is often perceived as difficult because it is commonly taught as an abstract concept and is not sufficiently connected to real-life technological applications. This study aimed to develop interactive multimedia on sublimation topics oriented toward chemical literacy and to examine its validity and initial feasibility. The study employed a Design-Based Research approach using the ADDIE model and was limited to the analysis, design, and development stages. The product was developed using Articulate Storyline 3 and was designed to integrate four aspects of chemical literacy: chemical concepts, chemical contexts, chemical processes, and scientific attitudes. Data were collected through validation and feasibility questionnaires. Validation was conducted by material and media expert lecturers, while the limited feasibility test involved 15 Chemistry Education students who had completed the Organic Chemistry I course. The validation results showed that the developed multimedia was valid, with an average r-count value of 0.81 across the learning, chemical literacy-oriented material substance, and display and software aspects. The limited feasibility test showed an average percentage of 91%, indicating that the multimedia was highly feasible for initial use in learning. These findings suggest that the developed interactive multimedia has adequate validity and initial feasibility as a learning medium for sublimation topics oriented toward chemical literacy. Further studies are needed to examine its effectiveness in improving learning outcomes and chemical literacy skills.